Stem Cell Development: Recent Improvements - Folorunso, Segun Stephen; Ogbe, David Oluwasegun; Udeh, Godwin Iheanacho; Shitta, Saheed Omobowale; Adeniran, Adetayo Olaniyi (Biocompounds, 2024)
In the early stages of life and growth, stem cells possess the remarkable ability to differentiate into a wide variety of cell types found in the body. Understanding the biochemical and metabolic processes, as well as the feedback linked to various stem cell responses, has advanced significantly. Limited cell survival, senescence-induced genetic instability or loss of function, and immune-mediated rejection are some of the difficulties associated with transplanted embryonic and Mesenchymal Stem Cells (MSCs). This study provides an overview of the most current knowledge and developments on stem cell development. Currently, research on stem cell treatment is being conducted for almost all human body tissues and organ types. Professionals with expertise in cell harvesting, culture, expansion, transplantation, and polymer design are crucial for the effective use of stem cell technology, as it currently encompasses the domains of engineering, materials science, and transplantation. Varying stem cell treatments are in varying phases of development; some are in preclinical studies, others are in clinical usage, and some are still in the discovery phase. Recent developments indicate that stem cell treatment may eventually have broader clinical relevance since it offers a promising therapeutic alternative for patients with a variety of degenerative diseases who need the replacement of lost tissue and cells. The discipline of regenerative medicine is a comprehensive scientific subject that has emerged more recently because of significant advancements in stem cell biology, tissue engineering, and nuclear transfer procedures. However, before initiating therapeutic uses, a deeper comprehension of the biology, manipulation, and safety of stem cells in tissue regeneration and repair is necessary.